Storm surges in the Alaskan Beaufort Sea - Reimnitz, Erk.; Maurer, Douglas K.; Geological Survey (U.S.) (Menlo Park, Calif. : U.S. Dept. of the Interior, Geological Survey, 1978)
Mode of access: Internet.